Like Taking a Magnifying Glass Into Everyday Life: Vulnerable Parents’ Experiences With Video Guidance in an Infant Mental Health Clinic - Simhan, Indra; Vik, Kari; Veseth, Marius; Hjeltnes, Aslak (Frontiers in Psychology, 2021)
Background: Parents are a central focus in clinical infant mental health interventions because of the key importance of the caregiver-infant relationship, especially when dyads are burdened by psychosocial and parental mental health problems. However, knowledge is scarce about the lived experience of vulnerable parents who undergo video-based guidance. Aim: The study explores how parents in an infant-psychiatric outpatient clinic who struggled to mentalize and remain emotionally connected to their infant experienced helpful and challenging elements in video guidance. Method: We analyzed the interviews of a strategic sample of twelve parents after undergoing Marte Meo video guidance, using a team-based, reflexive thematic analysis. Results: We identified four main themes: a) Handling initial feelings of fear and loss of control; b) Filming as a disturbing or agentic experience; c) Feeling validated or devalued in the therapeutic relationship; and d) Bringing insights from video guidance into everyday life. Therapeutic and existential factors became apparent in the main themes of adjustment to the guidance, experiences with filming, the therapeutic relationship and integration of new experiences. Conclusion: The parents’ sense of agency, dignity and shame may be important for their ability to integrate new ideas about themselves. Implications: Video guidance for vulnerable parents in specialized clinical treatment should address relational challenges, parental mental health, and issues of recognition.